Path and boundary of the influence of social entrepreneurial opportunity identification on the growth of commercial startups - Junjie, Wu; Yawei, Zhang; Qiao Qiao, Ding (Frontiers in Environmental Science, 2022)
Social entrepreneurship, as a way for enterprises to fulfill social responsibility, is becoming one of the key means to reconcile social contradictions in China. In the field of social entrepreneurship as entrepreneurship research focus in the emerging background, such as type business start-ups face “vulnerable” new defects, social entrepreneurship, how to deal with scarce resources, social entrepreneurship resources come from and how to create such basic problems as what kind of results is still not well explain, related research is still in a state of “cumulative pieces”. Therefore, this paper focuses on the social opportunity identification of commercial new ventures, and empirically analyzes the mechanism of social entrepreneurial opportunity identification and resource patchwork on their growth. The results demonstrate that finding social entrepreneurial opportunities is an important part of how resource collages can help social enterprises grow, and the entrepreneur’s social network allows for the mediating effect of resource collage. The more sources of “strong relationships” in entrepreneurs’ social networks, the stronger the impact of social entrepreneurial opportunity identification on the growth performance of commercial startups. Focusing on the field of corporate social entrepreneurship, our findings establish a complete chain of social entrepreneurship processes, from motivation to behavior to corporate sustainability. The findings confirm the mechanism by which social entrepreneurial opportunity identification and resource patchwork help to improve the growth performance of commercial new ventures, and also suggest that entrepreneurs’ social networks can relieve entrepreneurs’ dependence on external network construction to a certain extent.